Megacities and the Environment - Ethan H. Decker; Scott Elliott; Felisa A. Smith (The Scientific World Journal)
The world’s 25 largest cities comprise only 4% of the global population, but they have substantial impacts on the environment at multiple scales. Here we review what is known of the biogeochemistry of these megacities. Climatic, demographic, and economic data show no patterns across cities, save that wealthier cities have lower growth rates. The flows of water, fuels, construction materials, and food are examined where data are available. Water, which by mass dwarfs the other inputs, is not retained in urban systems, whereas construction materials and food predominate in the urban infrastructure and the waste stream. Fuels are transformed into chemical wastes that have the most far-reaching and global impacts. The effects of megacity resource consumption on geologic, hydrologic, atmospheric, and ecological processes are explored at local, regional, and global scales. We put forth the concepts of urban metabolism and urban succession as organizing concepts for data collection, analysis, and synthesis on urban systems. We conclude that megacities are not the final stage of urban evolution; rather, the climax of urban development will occur at a global scale when human society is at steady state with resource supply rates.